The Diagnosis of Knee Pain (Res Medica, 2014)
The knee is open to injury because it is designed for rapid action, not simply during its large excursion from extension to full flexion, but also lesser accommodative movements of rotation, tilt and glide. As if that were not enough, that highly developed but sometimes temperamental sesamoid, the patella, adds its own unique problems. The complexities of these movements are reflected in the subtleties of the structure of the knee. Regrettably they have also led to a proliferation of clinical tests and surgical repairs whose sophistication confuses rather than enlightens.Before enquiring about the characteristics of the painful knee the general characteristics of the patient should be assessed quickly. In children problems usually relate to patellar malalignment syndromes, possibly a discoid meniscus, and the aching discomfort produced by traction apophysitis such as Osgood-Schlatter's disease of the tibial tuberosity. After puberty girls are particularly likely to develop patellar pain, which may be associated with lateral subluxation of that bone. In the young woman the sources of such pain may be so prolix that the surgeon may do more harm than good if he operates. During adolescence and early adult life males are most likely to suffer from meniscal and ligamentous tears, often brought on by exertion or accidents during sport. A patient with an endomorphic physique usually has associated genu valgum and may present with medial ligament sprains and patello-femoral pain. Those with ligamentous laxity are also prone to sprains and patellar subluxation. The mesomorphic athlete is likely to injure the menisci, or may come in with significant tears of the ligaments and synovium.